FTIR ANALYSIS OF ACTIVATED CARBON PRODUCED USING VARIOUS REAGENTS (Universal International Scientific Journal, 2026)
In this study, activated and non-activated carbon samples obtained using different chemical reagents, KOH and ZnCl₂, were analyzed using Fourier transform infrared spectroscopy (FTIR). Spectra were recorded in the wavenumber range of 4000–700 cm⁻¹, and the composition of surface functional groups and their changes were analyzed comparatively.The results showed that the type of chemical activating reagent has a significant impact on the ratio of hydroxyl, carbonyl, aromatic, and ether groups on the carbon surface. It was found that activation using KOHpromotes the development of an aromatic structure, while activation using ZnCl₂ensures the preservation of oxygen-containing functional groups.
Keywords: activated carbon; FTIR; KOH